2012
DOI: 10.1113/expphysiol.2012.069989
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine infusion for postresuscitation blood pressure support after profound asphyxia in near‐term fetal sheep

Abstract: New Findings r What is the central question of this study?Dopamine is commonly used for blood pressure support in the neonate, but there is limited empirical evidence that it prevents hypotension or improves survival after asphyxia. r What is the main finding and its importance? Dopamine infusion delayed but did not prevent terminal hypotension after severe asphyxia in near-term fetal sheep. We also demonstrate that hypotension is directly associated with exacerbated brain swelling, strongly supporting the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(47 reference statements)
4
8
0
Order By: Relevance
“…Previous studies of such a prolonged duration of UCO in fetal sheep at the same gestational age as the present study have reported relatively short periods of recovery, likely because of this high mortality [20], [35], [36]. This is also broadly consistent with the typical clinical experience of 30 to 40% mortality after moderate to severe HIE [9], [37], [38].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies of such a prolonged duration of UCO in fetal sheep at the same gestational age as the present study have reported relatively short periods of recovery, likely because of this high mortality [20], [35], [36]. This is also broadly consistent with the typical clinical experience of 30 to 40% mortality after moderate to severe HIE [9], [37], [38].…”
Section: Discussionsupporting
confidence: 91%
“…Approximately one third of fetuses in the present study died either immediately after UCO or during recovery, similarly to our previous report [20]. Previous studies of such a prolonged duration of UCO in fetal sheep at the same gestational age as the present study have reported relatively short periods of recovery, likely because of this high mortality [20], [35], [36].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations